Effects of application of rapeseed cake as organic fertilizer on rice quality at high yield level. (12th September 2021) - Zhou, Tianyang; Chen, Liang; Wang, Weilu; Xu, Yunji; Zhang, Weiyang; Zhang, Hao; Liu, Lijun; Wang, Zhiqin; Gu, Junfei; Yang, Jianchang
Abstract: BACKGROUND: Applying organic fertilizer coupled with chemical fertilizer has been widely adopted to improve crop productivity and quality and develop sustainable agriculture. However, little information is available about the effects of organic fertilizer on the grain quality of rice ( Oryza sativa L.), especially nutritional quality and starch quality. In the present study, high yielding 'super' rice cultivars were grown in the field with three cultivation practices, including zero nitrogen application (0N), local high yielding practice with chemical fertilizer (T1) and T1 treatment with additional organic fertilizer (T2). RESULTS: Application of organic fertilizer synergistically improved rice production, nitrogen use efficiency, milling and appearance quality, and nutritional quality, including the contents of glutelin, essential amino acids and microelements, and also increased amylopectin and the ratio of the short chain of amylopectin, leading to a reduction in relative crystallinity, and decreased prolamin content. Application of organic fertilizer also increased the viscosity and breakdown values, whereas it decreased the pasting temperature and gelatinization enthalpy, resulting in better cooking and eating quality. CONCLUSION: Overall, application of organific fertilizer could synergistically improve nitrogen use efficiency and grain quality, including the structure and physicochemical properties of starch, contents of high value protein and amino acids, contents of microelements, and cooking and eating quality. © 2021 Society of Chemical Industry.